Phytophagous gall midges (Diptera, Cecidomyiidae) of Dagestan: fauna, biology and distribution - Z. A. Fedotova; G. M. Nakhibasheva; G. M. Mukhtarova; A. G. Gasangadzhieva (Юг России: экология, развитие)
Aim. Based on original and bibliographic data, to compile a review of the fauna of gall midges in Dagestan, Russia, including information about host plants, gall formation, life cycles and distribution.Materials and Methods. The basis for the work were materials collected in the flat and mountainous parts of Dagestan. Standard methods were used: inspection of the plants, search and mass collection of galls and damage to plants in which larvae develop; rearing imago; making permanent preparations of larvae and adults.Results. For the first time, an overview of the gall midges of Dagestan is offered. 67 species of gall midges of 41 genera were identified, of which 39 species are new to Dagestan, including 13 species new to the Caucasus: Asphondylia   hornigi   Wachtl,   1880,   A.   menthae   Kieffer,   1902,   A. salviaflorae Fedotova, 2003, Lasioptera eryngii (Vallot, 1829), Rosomyia spiraeae Fedotova, 1987, Dracunculomyia saissanica Fedotova, 1999, Dasineura plicatrix (Loew, 1850), D. sisymbrii (Schrank, 1803), D. trifolii (Löw, 1874), D. tamaricicarpa Fedotova, 1983, Asiodiplosis hodukini Marikovskij, 1965, A. petrosimoniae (Fedotova, 1994), Seriphidomyia butakovi  Fedotova,  2000.  Of  these  the  last  4  are  new  to  Russia. Phytophage gall midges (64 species of 36 genera) were found on plants belonging to 23 families, 46 genera and 56 species. Of the 36 genera of gall midges, 28 (77.8%) are plant‐specific to plant families, including 9 out of 28 (32.1%) monotypic. The fauna is based on the Western Palearctic and Turanian species.Conclusion. A preliminary review of gall midges in Dagestan in comparison with data on adjacent territories, indicates a very poor study of gall midges in general. Identification of the species diversity and trophic relationships of gall midges which develop on adventitious, invasive and economically important plants of the Caucasus is relevant both for protected natural areas and recreational areas.